Designing Surveillance Law - Bellia, Patricia L. (2011)
As communications surveillance techniques become increasingly important in government efforts to detect and thwart criminal and terrorist activities, questions of how to reconcile privacy and law enforcement interests take on paramount importance. These questions have institutional as well as substantive dimensions. That is, the issue is not simply what the limits on communications surveillance should be, but who should set them — courts through application of the Fourth Amendment or legislatures through statutes and the oversight process? The scholarly literature offers divergent positive and normative perspectives on these questions. For most scholars, the question of who should regulate communications surveillance activities has a straightforward answer: the task is one for the courts applying the Constitution. Because constitutionally-based regulation of communications surveillance tactics has been relatively limited since the seminal case of Katz v. United States in 1967, such scholars view the surveillance law landscape as one reflecting judicial abdication: courts have largely failed at reining in executive discretion and must play a more active role. For a handful of other scholars, in contrast, the limited constitutionally-based regulation of surveillance tactics is not a cause for concern. Such scholars argue for legislative supremacy in surveillance law on the theory that courts lack the expertise to evaluate rapidly evolving technologies.Explicitly or implicitly, discussions about the respective roles of courts and the legislature in policing surveillance tactics rest on premises about the comparative competence of those institutions to limit executive discretion. These inquiries into questions of institutional competence add an important perspective to the study of communications surveillance law — but, I argue, one that is ultimately incomplete. Such inquiries tend to take institutional structure as a given, thereby predicting the quality of decisions while bracketing questions of institutional design that could themselves influence the quality of decisions. In short, institutional competence analyses of communications surveillance law seek to choose the institutional decision-maker best suited to arrive at first-order policy preferences, but they neither take account of nor generate constraints on the second-order design choices available to implement those preferences. This article seeks to bring second-order design questions to the forefront of the surveillance law debate and to provide a framework for considering these questions